CRISPR beyond Editing: Innovative Applications in Medicine and Agriculture - Aliwi, Ghafran walled Awad; Lazim, Israa Mohammed Karim; farhan, Ahmed wleed sadiq; Jeber, Zahraa Hafde Fadhel (American Journal of Biology and Natural Sciences, 2024)
CRISPR is a versatile technology for editing genes originally discovered in bacteria as a component of their immune system. In a very short period, it has gone through numerous advancements and is presently applied not only in editing genes but also in many other innovative applications in the fields of agriculture and medicine.